2018
DOI: 10.1111/mpp.12725
|View full text |Cite
|
Sign up to set email alerts
|

A conserved motif promotes HpaB‐regulated export of type III effectors from Xanthomonas

Abstract: The type III secretion (T3S) system, an essential pathogenicity factor in most Gram-negative plant-pathogenic bacteria, injects bacterial effector proteins directly into the plant cell cytosol. Here, the type III effectors (T3Es) manipulate host cell processes to suppress defence and establish appropriate conditions for bacterial multiplication in the intercellular spaces of the plant tissue. T3E export depends on a secretion signal which is also present in 'non-effectors'. The latter are secreted extracellula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 68 publications
(103 reference statements)
2
16
0
Order By: Relevance
“…Interestingly, a recent study has shown that many recently discovered T3Es target to bacterial membrane where chaperone HpaB promotes recognition of T3Es by T3SS [ 23 ]. The free HpaB targets to the cytoplasmic and/or inner components of T3SS, which presumably is used to regulate secretion and/or translocation of T3SS substrates [ 11 , 12 , 14 , 22 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, a recent study has shown that many recently discovered T3Es target to bacterial membrane where chaperone HpaB promotes recognition of T3Es by T3SS [ 23 ]. The free HpaB targets to the cytoplasmic and/or inner components of T3SS, which presumably is used to regulate secretion and/or translocation of T3SS substrates [ 11 , 12 , 14 , 22 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a recent study has shown that many recently discovered T3Es target to bacterial membrane where chaperone HpaB promotes recognition of T3Es by T3SS [23]. The free HpaB…”
Section: The C-terminal Domain Of Hpab Is Dispensable For Interaction With T3ss Components In Xccmentioning
confidence: 99%
See 1 more Smart Citation
“…Notably, an interaction with T3S chaperones was also described for FliJ, Spa13, and InvI, suggesting that HrpO/FliJ/YscO family members are involved in a network of interactions with T3SS components and chaperones (Evans et al, ; Evans & Hughes, ). In Xcv , the T3S chaperone HpaB is essential for the efficient secretion and translocation of multiple effector proteins and was previously identified as interaction partner of T3SS components including the ATPase, the C ring, and the cytoplasmic domains of components of the export apparatus (Büttner et al, ; Büttner et al, ; Hartmann & Büttner, ; Lonjon et al, ; Lorenz & Büttner, ; Lorenz et al, ; Prochaska et al, ). The presence of multiple binding sites for HpaB in the T3SS suggests that HrpB7 does not play an exclusive role in the recruitment of chaperone complexes but might rather be of general importance for T3S.…”
Section: Discussionmentioning
confidence: 99%
“…Hrc and Hrp proteins are essential for T3S as structural components, whereas the accessory Hpa (Hrp associated) proteins are often involved in the control of T3S. One example is the T3S chaperone HpaB, which binds to type III effectors and presumably targets them to the T3S ATPase (Büttner et al, 2004;Büttner et al, 2006;Lonjon et al, 2017;Lorenz & Büttner, 2009;Prochaska et al, 2018;Scheibner et al, 2018). HpaB contributes to the translocation of most effector proteins and is, therefore, essential for pathogenicity.…”
Section: Introductionmentioning
confidence: 99%